Developing a Model for Assessing the Performance Outcome for Building Urban Community Resilience Through Public–Private Partnership - Robert Osei-Kyei; Godslove Ampratwum (Buildings, 2025)
The vulnerabilities of critical infrastructure and other disruptive events expose urban communities to severe risks. Public–private partnership (PPP) is an intensive cooperation between public and private actors with enhanced and more innovative services and policy outputs that can be achieved in building urban community resilience. Considering the potential of building urban community resilience through PPP, there is a need to assess the performance of using PPP in urban community resilience building. This study aims to develop a model for assessing the performance outcome for building urban community resilience through PPP. A questionnaire survey was conducted with experienced practitioners globally. The fuzzy synthetic evaluation method was used to develop an evaluation tool that could be used to objectively assess performance outcomes of PPP in urban community resilience building. The tool consists of five critical assessment indicators with defined coefficients: “Resilient urban community physical capital (0.270)”, “Well-developed community stakeholder engagement and training policies” (0.215), “Strong urban community disaster resilience PPP policy” (0.202), “Restriction and preservation” (0.197), “Existence of effective urban disaster risks database and PPP communication plan” (0.116). This performance assessment model can be used as a baseline for measuring the performance of PPP in urban community resilience building.